Strengthening Forensic Laboratory Methods in Solving Murder Case Without Witnesses: Case Study Polrestabes Bandung Jurisdiction - Abdur Roni Satya Pratama; Arthur Josias Simon Runturambi (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This study examines strengthening Scientific Crime Investigation (SCI) approaches through forensic laboratory methods for solving witness-less murder cases in Polrestabes (Metropolitan Police Resort) Bandung’s jurisdiction. The case study focuses on Police Report LP/B/421/XII/2024/JBR/Restabes BDG/Sektor Batununggal, involving victim MMY who died from neck slashing and back stabbing by an unknown perpetrator. Forensic laboratory methods serve as central pillars of SCI approaches. Without eyewitness testimony, scientific analysis of physical evidence becomes the sole objective means of uncovering facts. Forensic laboratories enable precise analysis of DNA, fingerprints, blood, fibers, and digital traces which potentially identifying suspects or supporting alibis. These laboratories accelerate investigations while enhancing legal evidence validity through scientifically accountable methods. Strengthening forensic laboratory facilities, human resources, and operational systems is crucial for effective law enforcement in witness-less homicide cases. The study employs a qualitative case study approach based on the Polrestabes Bandung case. Data collection includes literature reviews, interviews with investigators and experts, and investigation document analysis. This analysis aims to provide recommendations for strengthening forensic laboratory method utilization in witness-less homicide investigations. The research expects to deliver concrete recommendations for enhancing forensic laboratory method implementation in similar cases, providing replicable insights for police investigators. Additionally, it aims to contribute to strategic policy development regarding forensic laboratory methods within law enforcement institutions, ultimately improving the effectiveness of criminal investigations when traditional witness testimony is unavailable.